Sosialiasi Penjatuhan Pidana Penjara Bagi Pelaku Kekerasan Dalam Rumah Tangga Yang Telah Melakukan Mediasi - F, Fitriani (Yayasan Daarul Huda Kruengmane, 2024)
Law Number 23 of 2004 concerning the Elimination of Domestic Violence provides a strong legal basis that makes domestic violence, which was originally a household matter, a State matter. For this reason, the idea arose of using penal mediation by seeking a win-win solution so that imprisonment must be avoided for the perpetrator so that the objectives of Article 4 letter d are achieved. Based on this, the problem in this paper can be formulated as: what is the basis for the judge's consideration of imposing a prison sentence on perpetrators of domestic violence who have been mediated in Decision Number 19/PID.SUS/2019/PN Sim? The research method used in this writing is the normative juridical research method or library research method. The results of the research show that imposing a prison sentence of 22 days on the perpetrator is very inappropriate. The opportunity to reconcile domestic violence cases in the District Court is open. The Criminal Procedure Code has provided an opportunity for judges to keep perpetrators out of prison. There are two provisions in the Criminal Procedure Code which can be used as a legal basis for the implementation of penal mediation, namely Article 14A and Article 14 C. By using Article 14A, judges can prevent domestic violence perpetrators from prison sanctions by only giving a suspended sentence of under one year that does not need to be served. And Article 14C requires perpetrators to cure violent behavior by undergoing counseling.